Kontribusi K.H. Kholil Bangkalan : Dunia Tasawuf dan Tarekat dalam Islamisasi Pulau Madura: Dunia Tasawuf dan Tarekat dalam Islamisasi Pulau Madura - Fisabilillah, Dita (Maliki Interdisciplinary Journal, 2025)
Islam entered Indonesia in the 7th century AD, traders from various countries began to spread Islam through trade routes. Indonesia's strategic geographical location is the main factor in the spread of Islam easily in this country. Gujarati, Arab, Chinese and Persian traders carried out the buying and selling process while preaching their beliefs. Islam touched Madura Island, which is located northeast of Java. The arrival of Islam on Madura Island was brought by Gujarati, Persian and Arab traders around the 15th century AD. Walisongo with a da'wah base around Madura Island such as Sunan Ampel and Sunan Giri had an influence in the process of Islamic penetration. The Walisongo gave birth to scholars who succeeded Islamic da'wah activities such as K.H. Kholil Bangkalan in Bangkalan, Madura. K.H. Kholil Bangkalan is a Sufi with a legendary karamah. He spread the teachings of Islam using a Sufism approach until he succeeded in forming generations of famous Muslims. The results of this research indicate that Kiai Kholil played an important role in the development of Sufism in Indonesia. Starting with developing the tarekat in Madura. Some opinions say that Kiai Kholil is not affiliated with the tarekat sector, but the author assumes that Kiai Kholil is affiliated with a sect of the Tarekat Qadariyah wa Naqsbandiyah (TQN). He succeeded in developing his Sufism thoughts consisting of tasamuh, tawazun, taadul, and tawasut in social life